ANALISIS TEMUAN PENELITIAN MENGENAI USIA OPTIMAL PEMEROLEHAN BAHASA KEDUA DALAM PERSPEKTIF PSIKOLINGUISTIK: SEBUAH SYSTEMATIC LITERATURE REVIEW - Herwinda Khoirunnisa; Fitri Jamilah (STKIP Subang, 2026)
Second language acquisition (SLA) is a complex process influenced by biological, cognitive, and environmental factors. One of the most fundamental debates in psycholinguistics concerns whether there is an optimal age that objectively supports successful L2 acquisition. This study aims to analyze empirical findings on the optimal age for second language acquisition using a Systematic Literature Review (SLR) approach with the PRISMA protocol. The selection process yielded 24 articles meeting inclusion criteria from 287 articles identified across Google Scholar, Scopus, ERIC, and DOAJ databases. Analysis reveals that early age (before 7 years) provides significant advantages in phonology and morphosyntax, consistent with Critical Period Hypothesis (CPH) predictions. However, cross-study findings also indicate that age is not the sole determinant of L2 acquisition success—factors such as linguistic aptitude, motivation, and exposure intensity play complementary roles. These findings carry implications for foreign language curriculum design in Indonesia, particularly in determining the starting age for English instruction at the primary level.